Ca2+-currents in human induced pluripotent stem cell-derived cardiomyocytes - effects of two different culture conditions - Ahmet Umur Uzun; Ahmet Umur Uzun; Ingra Mannhardt; Ingra Mannhardt; Kaja Breckwoldt; Kaja Breckwoldt; András Horváth; András Horváth; András Horváth; Silke Skytte Johannsen; Silke Skytte Johannsen; Arne Hansen; et al. (Frontiers Media S.A., 2016)
Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) provide a unique opportunity to study human heart physiology and pharmacology and repair injured hearts. The suitability of hiPSC-CM critically depends on how closely they share physiological properties of human adult cardiomyocytes (CM). Here we investigated whether a 3D engineered heart tissue (EHT) culture format favors maturation and addressed the L-type Ca2+-current (ICa,L) as a readout. The results were compared with hiPSC-CM cultured in conventional monolayer (ML) and to our previous data from human adult atrial and ventricular CM obtained when identical patch-clamp protocols were used. HiPSC-CM were 2-3 fold smaller than adult CM, independently of culture format (capacitance ML 45±1 pF (n=289), EHT 45±1 pF (n=460), atrial CM 87±3 pF (n=196), ventricular CM 126±8 pF (n=50)). Only 88% of ML cells showed ICa, but all EHT. Basal ICa density was 10±1 pA/pF (n=207) for ML and 12±1 pA/pF (n=361) for EHT and was larger than in adult CM (7±1 pA/pF (p<0.05, n=196) for atrial CM and 6±1 pA/pF (p<0.05, n=47) for ventricular CM). However, ML and EHT showed robust T-type Ca2+-currents (ICa,T). While (-)-Bay K 8644, that activates ICa,L directly, increased ICa,L to the same extent in ML and EHT, β1- and β2-adrenoceptor effects were marginal in ML, but of same size as (-)-Bay K 8644 in EHT. The opposite was true for serotonin receptors. Sensitivity to β1 and β2-adrenoceptor stimulation was the same in EHT as in adult CM (-logEC50: 5.9 and 6.1 for norepinephrine (NE) and epinephrine (Epi), respectively), but very low concentrations of Rp-8-Br-cAMPS were sufficient to suppress effects (-logEC50: 5.3 and 5.3 respectively for NE and Epi). Taken together, hiPSC-CM express ICa,L at the same density as human adult CM, but, in contrast, possess robust ICa,T. Increased effects of catecholamines in EHT suggest more efficient maturation.